ILC2s induce Treg but not Th2-type immunity through IL-33/ST2 pathway in pulmonary tuberculosis - Qifeng Li; Quan Wang; Zhenhua Xu (Journal of Infection in Developing Countries)
Introduction: We investigated the function of type 2 innate lymphoid cells (ILC2s) and IL-33 in pulmonary tuberculosis (PTB).